Optimalisasi peran mahasiswa melalui kuliah kerja nyata mandiri sebagai upaya mendukung pencegahan penularan Covid-19 pada masyarakat - Ika Pasca Himawati; Heni Nopianti; Diyas Widiyarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The Covid-19 pandemic has provided various changes in all areas of life. Therefore, support is needed from various parties in efforts to prevent and spread Covid-19. One of them is through the Kuliah Kerja Nyata program organized by university and carried out independently by students in their respective neighborhoods. As an intra-curricular program, KKN becomes a bridge in transferring theoretical concepts to practical life in society. Through mentoring carried out with Field Supervisors, students are asked to compile a program of activities that can produce output in the form of educational activities to products. The resulting output is expected to be a step in preventing transmission of Covid-19. The method used is interactive guidance, through Focus Group Discussions (FGD) and mentoring between lecturers and students. This is done as part of the consultation and assistance activities so that students who carry out KKN Mandiri can achieve the goals and objectives of the activity. Besides, the existence of the KKN application called SIKANDO which has been designed by the University is expected to be a monitoring tool during KKN.